Religious minorities in the Middle East : domination, self-empowerment, accommodation - Longva, Anh Nga; Roald, Anne Sofie (Social, economic, and political studies of the Middle East and Asia ;, 2012)
Focusing on the situation of both Muslim and non-Muslim religious minorities in the Middle East, this volume offers an analysis of various strategies of resilience and accommodation from a historical as well a contemporary perspective.